Effects of a regional décollement level for gravity tectonics on late Neogene to recent large-scale slope instabilities in the Foz do Amazonas Basin, Brazil. (August 2016) - Reis, A.T.; Araújo, E.; Silva, C.G.; Cruz, A.M.; Gorini, C.; Droz, L.; Migeon, S.; Perovano, R.; King, I.; Bache, F.
Abstract: Extra sets of 2D multi-channel seismic and chronostratigraphic data allowed us to undertake analyses of source to sink processes and triggering mechanisms of the gigantic megaslides previously documented off the NW and SE steep slope settings of the Foz do Amazonas basin. As these megaslides comprise two sets of stacked allochthonous masses within the Upper Miocene-Quaternary sedimentary record, they are now described as Mass-Transport Complexes (MTCs) and have been renamed the Amapá Megaslide Complex (AMC) and the Pará-Maranhão Megaslide Complex (PMMC) . Individual megaslides of both MTCs can mobilize up to kilometre-thick sedimentary series as allochthonous masses with distinct flow directions, degrees of sediment disruption and internal coherence. Megaslides spread downslope over areas as large as thousands of km 2, attaining dimensions comparable to the world's largest mass-transport deposits. Among all the megaslides, the basal and largest AM1 megaslide (AMC) stands as a quite unique example of mass-transport deposit in the basin, interpreted as a dominant carbonate allochthonous mass sourced from a mixed carbonate-siliciclastic platform. The instability was probably triggered between the late Miocene and the end of the Early Pliocene by the gravitational collapse of the mixed platform under its own weight, after successive subaerial exposures which generated karstification processes. Siliciclastic-type megaslides, on the other hand, are all sourced from large upslope slide and/or rotated blocks (up to 60 km wide in the case of the PMMC). The detachment of upslope blocks was triggered by structurally-induced seabed movements during the Mid Pliocene-Pleistocene (in the case of the PMMC) and during the Pleistocene (in the case of the AMC). All mapped features support the interpretation of sedimentary blocks which have undergone long lasting deformation, having been variably folded and faulted by the sliding along an overpressured condensed section (H3 horizon). H3 horizon equally acts as the upper décollement level for the gravity tectonic system that operates on the regional scale of the Foz do Amazonas basin. In such a context, the results of this study evidence complex links between variable modes and scales of gravity processes (gravity tectonics and MTCs emplacements), all induced by instability created from a condensed section prone to produce pore fluid overpressure. And yet, seismic attributes of the décollement H3 across the slope, characterized by a reflector of negative polarity of high amplitude, indicate that the potential for similar large scale sediment failures continues to exist across the AMC and PMMC. Highlights: Two gigantic megaslide complexes occur in the offshore Amazon basin. Megaslides involve the late Miocene-Pleistocene sedimentary succession. Gravity collapse of a carbonate platform triggers the basal and largest MTD. Décollement level for gravity tectonics also triggers siliciclastic MTDs. Potential for the occurrence of similar large scale MTDs still exists in the basin.